Inhibiting miR-129-5p alleviates inflammation and modulates autophagy by targeting ATG14 in fungal keratitis. (October 2021) - Lin, Jingqiong; Lin, Yi; Huang, Yurong; Hu, Jianzhang
Abstract: To investigate the role of miR-129-5p in inflammation and autophagy in fungal keratitis, we established a keratitis mouse model infected with Fusarium solani ( F. solani ) and conducted experiments on corneal stromal cells infected with F. solani . The expression of miR-129-5p was detected via quantitative real-time polymerase chain reaction (PCR). The miR-129-5p antagomir was used to transfect cells and mice to study the regulatory role of miR-129-5p in autophagy and inflammation after fungal infection. The expression of Beclin1 and LC3B and colocalization of LC3B with lysosomes were detected via Western blotting and immunofluorescence. CCK-8 was used to determine the viability of corneal stromal cells. The expression of IL-1β were detected by ELISA. Bioinformatics software was used to predict the potential targets of miR-129-5p, which were verified by a luciferase reporter gene assay. RT-PCR showed that miR-129-5p expression in mouse corneas was significantly increased after infection with F. solani . Subconjunctival injection of the miR-129-5p antagomir significantly enhanced the proteins Beclin-1 and LC3B. At the same time, inhibiting miR-129-5p expression could reduce the inflammatory response in FK and significantly increase the viability of corneal stromal cells infected with F. solan . Moreover, the dual luciferase reporter assay indicated that Atg14 was a direct target of miR-129-5p. Our study shows that miR-129-5p is a novel small molecule that regulates autophagy by targeting Atg14, indicating that it may be a proinflammatory and therapeutic target for fungal keratitis. Highlights: miR-129-5p expression in mouse corneal was significantly increased after infection with F. solani. Inhibiting miR-129-5p can enhance autophagy and reduce inflammatory response of corneal tissue. Results of dual luciferase reporter assay indicated that Atg14 is a direct target of miR-129-5p.